STUDENT’S ATTITUDE AND INTEREST TOWARDS LEARNING TULU SCRIPT - P, Gururaj; Kulal, Abhinandan; N, Abhishek; Kanchan, Swarn G (International Journal of Research -GRANTHAALAYAH, 2022)
Tulu language is the mother tongue of people in Karavali (costal) Karnataka. The inscriptions started that land from Neeleshwara to Ankola as Tulu Rajya; hence there is a need to recognize the Tulu language. Languages are also prime vehicles of cultural expressions and intangible cultural heritage, essential to the identity of individuals and groups; safeguarding endangered tongues were crucial in maintaining cultural diversity worldwide. People who are well educated will have an interest in learning new and challenging things. Paper made an earnest attempt to know the students’ interest in learning Tulu script, Level of Awareness, and Attitude towards learning Tulu script. The study was carried out in Karnataka by taking 400 students on a random basis. It found that there is a positive relation between Interest, Awareness, and Attitude.